A new species of Metacoelura (Collembola: Paronellidae) from Australia, and redescription of Metacoelura articulata - Ma, Yitong; Zhao, Chun; Greenslade, Penelope (Zootaxa, 2016)
The genus Metacoelura Salmon, 1951 is unusual as it possesses some characters typical of the family Entomobryidae and others of the Paronellidae. Three species and subspecies have been described, all from Australasian tropical regions. Metacoelura articulata is redescribed and a new species, Metacoelura majeri sp. nov., is described based on material collected in Australia. A key to species of the genus is provided.